Efficient Stable in Vitro Micropropagation and Conservation of Tinospora cordifolia (Willd.) Miers: an Anti-diabetic Indigenous Medicinal Plant - Chatterjee, Tuhin; Ghosh, Biswajit (International Journal of Bio-resource and Stress Management, 2023)
An efficient protocol is described for the rapid in vitro multiplication of Tinospora cordifolia (Willd.) Miers., an important indigenous medicinal plant, via enhanced shoot bud proliferation from shoot tip explants. This plant has great importance to different pharmaceutical industry for its medicinal value and mainly harvested from the wild population is resulting an over-exploitation of natural habits. To avoid this alarming situation and to ensure its continuous supply, plant tissue culture technique was applied. The explants cultured on to MS medium containing different concentrations of BAP, Kn and NAA either alone or in combination for investigation of morphogenetic response. The best shoot proliferation (16.5±0.25) was observed MS media supplemented with 5.0 mg l-1 BAP alone. The highest shoot elongation observed MS medium containing 1.0 mg l-1 BAP in combination with 0.6 mg l-1 GA3 (12.5±1.5 cm). The maximum rooting frequency (82.00±3.0%) obtained from the MS medium in the combination 1.0 mg l-1 IBA. For in vitro conservation, the best response (95%) was achieved using 2% sorbitol and 2% mannitol in combination with MS medium at 10 °C temperature up to 8 months by in vitro slow growth technique. Regenerated plantlets were transferred to greenhouse conditions and observed 90.00±0.4% survival frequencies. The diploid status (2n=24) of regenerated plantlets as well as mother plant was determined using chromosome counts of root-tips. Berberine content (0.218%) in regenerated plants was determined by using HPTLC and HPLC methods. It is concluded that the regenerated plants were stable in respect to their morphology, chromosome number and berberine content, which offers a unique opportunity to obtain true-to-type plants as source plant.